An aptamer array for discriminating tetracycline antibiotics based on binding-enhanced intrinsic fluorescence. Issue 7 (9th March 2023) - Zhao, Yichen; Gao, Biwen; Chen, Yijing; Liu, Juewen
Abstract : Ten DNA aptamers for tetracycline antibiotics studied using the intrinsic fluorescence. Using three of the aptamers, a sensor array is produced to discriminate tetracycline, oxytetracycline and doxycycline from each other and from other molecules. Abstract : Tetracyclines are a class of antibiotics with a similar four-ringed structure. Due to this structural similarity, they are not easily differentiated from each other. We recently selected aptamers using oxytetracycline as a target and focused on an aptamer named OTC5, which has similar affinities for oxytetracycline (OTC), tetracycline (TC), and doxycycline (DOX). Tetracyclines exhibit an intrinsic fluorescence that is enhanced upon aptamer binding, allowing convenient binding assays and label-free detection. In this study, we analyzed the top 100 sequences from the previous selection library. Three other sequences were found to differentiate between different tetracyclines (OTC, DOX, and TC) by the selective enhancement of their intrinsic fluorescence. Among them, the OTC43 aptamer was more selective for OTC with a limit of detection (LOD) of 0.7 nM OTC, OTC22 was more selective for DOX (LOD 0.4 nM), and OTC2 was more selective for TC (0.3 nM). Using these three aptamers to form a sensor array, principal component analysis was able to discriminate between the three tetracyclines from each other and from the other molecules. This group of aptamers could be useful as probes for the detection of tetracycline antibiotics.